State of Nationalism (SoN): Nation Branding - Nichole Fernández (Studies on National Movements, 2020)
Nation branding goes beyond simply government propaganda or tourism promotion, but rather consists of a multitude of activities that form a comprehensive, top-down, government driven and funded initiative that appropriates corporate branding strategies to a nation.